Pyruvate and uridine rescue the metabolic profile of OXPHOS dysfunction - Isabelle Adant; Matthew Bird; Bram Decru; Petra Windmolders; Marie Wallays; Peter de Witte; Daisy Rymen; Peter Witters; Pieter Vermeersch; David Cassiman; Bart Ghesquière (Elsevier, 2022)
Introduction: Primary mitochondrial diseases (PMD) are a large, heterogeneous group of genetic disorders affecting mitochondrial function, mostly by disrupting the oxidative phosphorylation (OXPHOS) system. Understanding the cellular metabolic re-wiring occurring in PMD is crucial for the development of novel diagnostic tools and treatments, as PMD are often complex to diagnose and most of them currently have no effective therapy. Objectives: To characterize the cellular metabolic consequences of OXPHOS dysfunction and based on the metabolic signature, to design new diagnostic and therapeutic strategies. Methods: In vitro assays were performed in skin-derived fibroblasts obtained from patients with diverse PMD and validated in pharmacological models of OXPHOS dysfunction. Proliferation was assessed using the Incucyte technology. Steady-state glucose and glutamine tracing studies were performed with LC-MS quantification of cellular metabolites. The therapeutic potential of nutritional supplements was evaluated by assessing their effect on proliferation and on the metabolomics profile. Successful therapies were then tested in a in vivo lethal rotenone model in zebrafish. Results: OXPHOS dysfunction has a unique metabolic signature linked to an NAD+/NADH imbalance including depletion of TCA intermediates and aspartate, and increased levels of glycerol-3-phosphate. Supplementation with pyruvate and uridine fully rescues this altered metabolic profile and the subsequent proliferation deficit. Additionally, in zebrafish, the same nutritional treatment increases the survival after rotenone exposure. Conclusions: Our findings reinforce the importance of the NAD+/NADH imbalance following OXPHOS dysfunction in PMD and open the door to new diagnostic and therapeutic tools for PMD.